2016
DOI: 10.1039/c5cy01418b
|View full text |Cite
|
Sign up to set email alerts
|

Highly active electron-deficient Pd clusters on N-doped active carbon for aromatic ring hydrogenation

Abstract: Pyridinic nitrogen species in N-doped active carbon (xN-AC) are responsible for high activity of ring hydrogenation via the formation of a high percentage of electron-deficient Pd clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 49 publications
3
70
0
1
Order By: Relevance
“…The small size of Pt clusters may also result in suitable H‐spillover effect for further improving the activity than larger Pt particles . In addition, the strong interaction between Pt clusters and support would result in lower reducibility of Pt species with a relative electron‐deficient structure, thus promoting the adsorption of hydrogen and leading to high hydrogenation activity . Based on the hydroisomerization mechanism of n ‐alkanes, the small size and high dispersion of Pt can effectively enhance contact chance between Pt and acid sites .…”
Section: Resultsmentioning
confidence: 99%
“…The small size of Pt clusters may also result in suitable H‐spillover effect for further improving the activity than larger Pt particles . In addition, the strong interaction between Pt clusters and support would result in lower reducibility of Pt species with a relative electron‐deficient structure, thus promoting the adsorption of hydrogen and leading to high hydrogenation activity . Based on the hydroisomerization mechanism of n ‐alkanes, the small size and high dispersion of Pt can effectively enhance contact chance between Pt and acid sites .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, some researchers have reported that the emerged nitride functional groups on the carrier are beneficial to improving the properties of the third functional component through constructing the interaction between nitride groups and other functional species just like the metal ions, nanoparticles or complexes . For example, Datta et al., demonstrated that the Au nanoparticles were successfully embedded in MCN due to the nitride groups on the MCN walls providing a platform for constructing special metal nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a large number of heterogeneous supports e. g. porous silica, nanoporous organic polymers (POPs), metal oxides, N‐doped activated carbon, amorphous carbon etc. are reported, which shows quite promise and potential in anchoring metal NPs for catalysis, but hierarchical micro‐mesoporous support with uniform hollow nanostructure could be more promising…”
Section: Introductionmentioning
confidence: 99%